Urban planning and social role of physical culture and sports zones of higher education institutions in the context of sustainable development - Agieieva, Galyna; Chernisheva, Mariia; Korobko, Kateryna (Theory and practice of design, 2021)
he paper examines the impact of physical culture and sports zones (hereinafter — PSZ) of higher education institutions on the environment of total urbanization and the possibility of creating a kind of clusters of positive changes in the social structure of the metropolis. The purpose of the work is to determine the main town-planning, architectural planning decisions of the National Aviation University (hereinafter — NAU), to investigate its role in the formation of one of the main components of the concept of sustainable development - the social climate of the location; propose additional measures to strengthen the role of the NAU PSZ in improving the social climate of the location. Objectives of the study. To achieve this goal, the following tasks are solved: to search and analyze archival materials, design and operational documentation; to analyze the urban situation that has developed over the past decades; to analyze the technical condition of PSZ facilities and assess the possibility of providing them with additional functions. Research methods — study of cartographic, photographic and design materials; processing information on the history of construction and operation of the object of study; generalization of personal experience of using the services of the object of research and volunteer work during mass social events; comparative and critical analysis, a systematic approach to the study of the object as a complex and identify its properties and relationships with the environment. Results. The data that characterize the object of study as a component of the university, and its role in the urban situation and social environment are analyzed. Changes in the structure and load of the PSZ service area related to the compaction of the building located near the university have been identified and assessed. The influence of open territories of PSZ and green spaces of NAU on formation of favorable microclimatic conditions and improvement of ecological condition of environment is estimated. The technical condition of PSZz facilities has been assessed. Variants of re-equipment of spectator seats (stands) of the stadium are offered. Possibilities of strengthening the social function of the PSZ, providing socially oriented services of irregular consumption, etc. have been identified. Scientific novelty. Based on a systematic approach to the study of the urban situation, the social environment, it is proposed to create a kind of clusters of positive changes in the social structure of Kiev, in particular, Solomyansky district. To do this, it is necessary to restore the serviceability of buildings and structures of the PSZ NAU, combine them functionally with the construction of new and reconstruction of existing cultural — entertainment and leisure facilities located nearby and built in the 1970-1980s. Practical significance. The obtained results can be used in further research of the peculiarities of the formation and reorganization of the PSZ IHE; urban and social changes in their areas of influence; finding new forms of strengthening the social functions of the PSZ and providing socially oriented services of irregular consumption. The creation of clusters of positive changes in the social environment, which may include PSZ institutions of higher education, requires further and deeper study within the urban issues of scientific research NAU. Practical significance. The obtained results can be used in further research of the peculiarities of the formation and reorganization of the PSZ IHE; urban and social changes in their areas of influence; finding new forms of strengthening the social functions of the PSZ and providing socially oriented services of irregular consumption. The creation of clusters of positive changes in the social environment, which may include PSZ institutions of higher education, requires further and deeper study within the urban issues of scientific research NAU.